Warehouse management model based on Lean Warehousing to improve perfect order fulfillment in a pharmaceutical warehouse (LACCEI, 2024)
This study focuses on the correct service management of pharmaceutical warehouse processes since an excellent level of service is required in the correct distribution of orders without interrupting the flow of deliveries to customers. This problem becomes more relevant because involve medicines. For this reason, the level of perfect order fulfillment was analyzed, of which it presents a % of 85% compared to 95% of the required sector, which this gap is equivalent to S /. 411,451 in lost sales due to penalties and returns. As a contribution, Lean Warehousing tools such as 5s, standardization, Poka Yoke and TPM were implemented in the warehouse processes following a continuous improvement methodology. The solutions presented for each root cause were measured based on indicators of the perfect order, such as the percentage of complete deliveries, the percentage of quality deliveries, the percentage of on-time deliveries, and the percentage of adequate documentation. In conclusion, the application of the improvement proposal will increase the percentage of perfect orders above 95% of the standard of excellence, achieving a better flow of orders in a future VSM in less time and in a higher quality of service for the final customer.